(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Acute myeloid leukemia (AML) is a heterogeneous group of myelogenous disorders that result from the proliferation of immature monoclonal myeloblastic cells within the bone marrow and their spread to the peripheral blood and to other organs. The development in genetic techniques has greatly contributed to our understanding of the mechanism of acute myeloid leukemia and its warning, especially in normal karyotype patients, and opened new horizons for the search for targeted treatments for these gene disorders responsible for the occurrence of the disease and perhaps its full treatment in the future, but so far these methods are still expensive in our society, which prompted us to search for prognostic factors that are easy to perform and inexpensive like determining the serum level of lactate dehydrogenase enzyme (LDH), so we studied in this research the association between serum LDH levels and the prognostic significance in AML patients, the study was conducted on 100 patients who reviewed the Division of Hematology and Oncology, in Tishreen University Hospital, a significant association was found between high levels of LDH, low survival and poor prognosis in these patients, and there was a relation between the presence of the FMS Like Tyrosine Kinase (FLT3) mutation and high levels of LDH, which indicates a link between the presence of this mutation and the bad prognosis. The accompanying disadvantages, we conclude from this study the importance of conducting LDH as a routine analysis of prognostic value in patients with AML.